2008
DOI: 10.1089/apc.2007.0247
|View full text |Cite
|
Sign up to set email alerts
|

Safer Sexual Behaviors after 12 Months of Antiretroviral Treatment in Mombasa, Kenya: A Prospective Cohort

Abstract: Roll-out of antiretroviral treatment (ART) raises concerns about the potential for unprotected sex if sexual activity increases with well-being, resulting in continued HIV spread. Beliefs about reduced risk for HIV transmission with ART may also influence behavior. From September 2003 to November 2004, 234 adults enrolled in a trial assessing the efficacy of modified directly observed therapy in improving adherence to ART. Unsafe sexual behavior (unprotected sex with an HIV-negative or unknown status partner) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
75
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 36 publications
17
75
3
Order By: Relevance
“…Therefore, strengthening the provision of secondary prevention messages and risk-reduction interventions in ART programs creates an enabling environment for reduction of risky sexual behaviours [13] [22]. Moreover, HIV-infected persons with longer duration on ART might use condoms consistently to protect their sex partners from infection [4] [6]. Our data further point out that the association between longer duration on ART and awareness of partner's HIV status is crucial in the reduction of risky sexual behaviour among HIV-infected persons on ART.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, strengthening the provision of secondary prevention messages and risk-reduction interventions in ART programs creates an enabling environment for reduction of risky sexual behaviours [13] [22]. Moreover, HIV-infected persons with longer duration on ART might use condoms consistently to protect their sex partners from infection [4] [6]. Our data further point out that the association between longer duration on ART and awareness of partner's HIV status is crucial in the reduction of risky sexual behaviour among HIV-infected persons on ART.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that access to ART has not led to significant reductions in risky sexual behavior among HIV-infected persons [2] [3] [6]. Moreover, there are concerns that providing ART may lead to an increase in sexual risk behaviours because of the improved quality of life associated with ART [1] [7].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 50 were excluded from the systematic review (for reasons such as unclear study designs, outcomes or unclear relationship between HAART and sexual behavior variables), but used in the literature review, while 28 were entirely excluded. Finally, 14 articles [6][7][8][19][20][21][22][23][24][25][26][27][28][29] met the criteria for inclusion in this review as primary articles.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies had low rigor, as only three [21,22,24] scored at least 5 on methodological rigor. Limitations found in the reviewed studies were reliance on self-report of sexual behaviors, convenience, consecutive or other non-random sampling, assessment of health facility-based populations, and failure to adjust for major confounding variables or failure to assess any interaction effects in the predictor variables.…”
Section: Methodological Rigormentioning
confidence: 99%
See 1 more Smart Citation